Mechanisms of ferroptosis in nonalcoholic fatty liver disease and therapeutic effects of traditional Chinese medicine: a review - Wang, Nan; Que, Hanyun; Luo, Qiulin; Zheng, Wenxin; Li, Hong; Wang, Qin; Gu, Jian (Frontiers in Medicine, 2024)
Nonalcoholic fatty liver disease (NAFLD) is characterized by excessive accumulation of fat in hepatocytes (nonalcoholic fatty liver (NAFL)), and lobular inflammation and hepatocyte damage (which characterize nonalcoholic steatohepatitis (NASH) are found in most patients). A subset of patients will gradually develop liver fibrosis, cirrhosis, and eventually hepatocellular carcinoma, which is a deadly disease that threatens human life worldwide. Ferroptosis, a novel nonapoptotic form of programmed cell death (PCD) characterized by iron-dependent accumulation of reactive oxygen radicals and lipid peroxides, is closely related to NAFLD. Traditional Chinese medicine (TCM) has unique advantages in the prevention and treatment of NAFLD due to its multicomponent, multipathway and multitarget characteristics. In this review, we discuss the effect of TCM on NAFLD by regulating ferroptosis, in order to provide reference for the further development and application of therapeutic drugs to treat NAFLD.